Precision Health: Transforming the Future of Healthcare in Qatar - Qatar Foundation (19330839) (2024)
This report is a product of more than a decade of visionary leadership in precision health initiated by Her Highness Sheikha Moza bint Nasser, Chairperson of Qatar Foundation. It was written through a collaboration between key experts across Qatar Foundation’s ecosystem. The overall coordination of the report as well as consultations, desktop research, and reviews were facilitated by Hanieh Khataee, Strategy and Impact Director with Jessica DuPlessis, Manager of Impact and Advisory Services. Expert consultations and technical reviews were carried out by members of the editorial committee from Hamad Bin Khalifa University, Qatar Precision Health Institute, Sidra Medicine, and Weill Cornell Medicine-Qatar. Other Information License: https://creativecommons.org/licenses/by/4.0/